The effect of open and distant learning educational systems on the students' locus of control in Payam-e-Noor University - Fereydoon Yazdani (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2010)
Introduction: Locus of Control refers to an individual's perception about the underlying main causes of events in his/her life. Individuals with a high internal locus of control believe that events result primarily from their own behaviour and actions. In contrasts, those with a high external locus of control believe that powerful others, fate, or chance primarily determine events. Some educators believe that human beings who have had independence or autonomy in their life, are more likely to have a more intrinsic locus of control than extrinsic. This research aims to determine whether educational methods applied in payam-e-noor university (as a distance education university) can ultimately change the students’ locus of control orientation. Materials and Methods: This study aimed to investigate the effects of instructional procedures of Payam-e-noor University (as a distance education system) on the change of students’ locus of control. The Research method was descriptive (survey research). In this study, data were collected based on the paper-pencil scale of Rotter‘s locus of control. The reliability of this scale, was formerly improved by specialists and also Movafagh normalized it in Iran. Moreover, in the present study, the reliability was checked by test-retest methods. The achieved correlation was relatively appropriate (r= 0.75). The statistical population of this study included all students (male and female) of payam-e-noor University, Nahavand branch. The students in their current semester have been enrolled and studied during the semester. Sampling was done using a combined method (simple random and clustering methods). Results: The results of this study indicated that there was a significant difference between junior student’s locus of control compared with the senior student’s locus of control. Also the study revealed that, there was not any significant difference between male and female students’ locus of control. Likewise, the research indicated that there was a significant difference between the students’ locus of control in different academic disciplines in this university. And finally between student’s age and their locus of control there was not any significant relationship. Conclusion: Considering the findings of this study it can be stated that the distant learning program at Payam-e-noor university has a positive effect in changing the students' locus of control, and this change differed in different fields.